Growth Status of Full-Term Infants with Different Sizes for Gestational Age During the First Year of Life - Zhou ZR; Guo Y (Dove Medical Press, 2024)
Zhuo-Ren Zhou, Yong Guo Department of Health Care, Guangdong Women and Children Hospital, Guangzhou, 511400, People's Republic of ChinaCorrespondence: Yong Guo, Department of Health Care, Guangdong Women and Children Hospital, Guangzhou, 511400, People's Republic of China, Tel +86 2039151521, Email geyong084@163.comObjective: This study aimed to assess the growth of full-term infants with different sizes at birth and examine catch-up and catch-down growth in their first year.Methods: This retrospective population-based cohort study was based on the Guangdong Provincial Women and Children Health Information System. 194797 full-term singleton live births were extracted. Measurements for weight and length were taken at birth, 6 months, and 12 months. The size-for-gestational age was categorized as small (SGA, < 10th centile), appropriate (AGA, 10th-90th centiles), or large (LGA, > 90th centile) based on the international newborn size for gestational age and sex INTERGROWTH-21st standards. Catch-up and catch- down growth were defined as a change in standard deviation in z-score greater than 0.67 in the growth curves.Results: Of the 194797 full-term singletons, the average gestational age was 39.28 ± 1.03 weeks, and the average weight of the newborns was 3205 ± 383 grams. 15632 infants were identified as SGA (8.0%) and 12756 were LGA (6.5%). At 1 year of age, catch-up growth in weight was observed in 63.0% of SGA infants, 29.5% of AGA infants, and 5.4% of LGA infants. Conversely, catch-down growth occurred in 3.3% of SGA infants, 17.8% of AGA infants, and 54.7% of LGA infants. The proportions of catch-up growth in length for SGA, AGA, and LGA infants within the first year were 31.4%, 22.5%, and 17.1%, respectively. Catch-up or catch-down growth predominantly occurred before 6 months of age. However, from 6 to 12 months, there was no significant variation in WAZ among children with different birth sizes.Conclusion: In their first year of life, full-term singleton live births tend towards regression to the mean in their postnatal weight and length. The average delay in the growth of LGA is compensated by an increase in it of the SGA. Early monitoring and intervention are crucial for optimizing growth in infants with different birth sizes.Keywords: growth status, infant, birth weight, catch-up growth